Co-containing metal organic framework with a linear bis-imidazole and dicarboxylate: Electrochemical and electrocatalytic properties. (15th October 2016) - Zhang, Chengyan; Wang, Jingjing; Zhang, Yongshun; Zhang, Xiaobo; Ma, Juanjuan; Liu, Lin; Xu, Xingyou
Graphical abstract: A new Co-MOF ([Co(BDC)(bib)] n ) was successfully prepared under hydrothermal conditions and the glass carbon electrode modified with the as-synthesized Co-MOF exhibits good redox activity and also displays good electrocatalytic activity for the oxidation of hydrogen peroxide. Abstract: A new Co-containing metal-organic framework (Co-MOF), [Co(BDC)(bib)] n (bib = 1, 4-bis-imidazolebenzene; H2 BDC = 1, 4-benzenedicarboxylic), has been synthesized under hydrothermal conditions. Its structural characterization was carried out by means of elemental analysis, infrared spectroscopy, thermogravimetric analysis, UV–Vis and single X-ray diffraction. The Co-MOF exhibits 2-fold interpenetrated sql topology, which is further stacked through hydrogen-bond interactions leading to the formation of a 3D supramolecular architecture. The CV results of [Co(BDC)(bib)] n modified electrode show a pair of redox peaks at ca. 0.13 V in 0.5 M NaOH solution and also display good electrocatalytic activity for oxidation of hydrogen peroxide in alkaline medium.